Economic Value Added Method as A Tools to Measure Financial Performance Assessment in PT. Campina Ice Cream Tbk. - Wulandari, Himza Fadhilah Putri (Quantitative Economics and Management Studies, 2021)
Every company established has a goal to gain profits and maximize wealth to shareholders. The purpose of this study is to analyze method of Economic Value Added as a measure of financial performance assessment at PT. Campina Ice Cream Industry Tbk. Method used in this study a Qualitative Descriptive approach. Data source in this study uses secondary data form of financial statements PT. Campina Ice Cream Industry Tbk in 2016-2018. Analysis data technique used is method of Economic Value Added. Economic Value Added shows the measurement of extent to which company has value added to owners of company in a given year or period. The results of this study can be concluded that Economic Value Added (EVA) at PT.Campina Ice Cream Industry Tbk in 2016 worth Rp. (3.656.510.875) and in 2017 valued at Rp. (2.473.733.162) so that it produces a negative Economic Value Added or> 0 which can be said that the company financial performance is not good. However, in 2018 company achieved scores. Economic Value Added <0 or positive worth Rp. 15.881.445.739 then, it can be concluded that company financial performance is good and has resulted in value added expected by the shareholders.